2019
DOI: 10.1038/s41598-019-53704-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Activation of Arabidopsis Zygotes Is Required for Initial Cell Divisions

Abstract: Commonly referred to as the maternal-to-zygotic transition, the shift of developmental control from maternal-to-zygotic genomes is a key event during animal and plant embryogenesis. Together with the degradation of parental gene products, the increased transcriptional activities of the zygotic genome remodels the early embryonic transcriptome during this transition. Although evidence from multiple flowering plants suggests that zygotes become transcriptionally active soon after fertilization, the timing and de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 91 publications
1
34
0
Order By: Relevance
“…5 a, c). Arabidopsis zygotes require de novo synthesis of gene products directly after fertilization [ 57 , 73 ], and genes involved in rRNA biogenesis produce high levels of transcripts in preglobular embryos relative to later stages [ 40 ]. In contrast to Arabidopsis, maternally donated proteins drive early embryogenesis in Xenopus and H1 dynamics mediate transcriptional activation of rRNA loci in oocytes and their silencing in somatic tissues [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 a, c). Arabidopsis zygotes require de novo synthesis of gene products directly after fertilization [ 57 , 73 ], and genes involved in rRNA biogenesis produce high levels of transcripts in preglobular embryos relative to later stages [ 40 ]. In contrast to Arabidopsis, maternally donated proteins drive early embryogenesis in Xenopus and H1 dynamics mediate transcriptional activation of rRNA loci in oocytes and their silencing in somatic tissues [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expansion microscopy technique [ 109 ] optimized for Arabidopsis seeds was conducted as previously described [ 73 ]. Anti-Fibrillarin antibody (ab4566, Abcam) and anti-alpha Tubulin antibody (ab89984, Abcam) were used in 1:500 dilution as primary antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…Other protocols focus on preservation and isotropic expansion of ultrastructure (U-ExM) (Gambarotto et al, 2019) or on precise tuning of the expansion factor between 2 and 8 (ZOOM) (Park et al, 2019). Recently, ExM has been applied also to bacterial pathogens (Kunz et al, 2019) and to plants (Kao and Nodine, 2019), paving the way for new methodological approaches in these fields.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several reports (Chozinski et al 2016;Cahoon et al 2017;Freifiled et al 217;Jiang et al 2018;Wang et al 2018b;Gambarotto et al 2019;Kao and Nodine 2019;Xu et al 2019;Zwettler et al 2020a, b) demonstrated the improved visualisation of target proteins after applying ExM. Thus, ExM can reveal the unaltered localization of target molecules, but preserving the chromatin ultrastructure of isolated nuclei is more challenging, and therefore, further improved ExM protocols have to be developed.…”
Section: Discussionmentioning
confidence: 99%